Graphic design before graphic designers : the printer as designer and craftsman: 1700-1914 - Jury, David (New York : Thames & Hudson, 2012)
International in scope, this book charts the evolution of print into graphic design between 1700 and 1914. With around 850 illustrations, many specially photographed from private collections, it is of interest to graphic designers, design and social historians, as well as collectors of print and printed emphemera alike.
boek